Sociodemographic Profile of Severely Malnourished Children Admitted to a Nutritional Rehabilitation Centre in One of the Districts of Maharashtra: A Cross-sectional Study - Pratik Borkar; Rohan Sangam; Shalini Rawat; Ravindra Kembali (Healthline)
Introduction: Globally malnutrition remains the one of the leading causes of mortality contributing to 60% of deaths in under five children. Severely acute malnutrition children are admitted to Nutritional rehabilitation centre for promoting their clinical and psychological growth. Objective: To describe the sociodemographic profile of severely malnourished children admitted in NRC. Method: The study was observational cross sectional study conducted in a Nutritional Rehabilitation Centre (NRC) of a District Hospital of Thane in Maharashtra among the under five children of age group 6 to 60 months who were admitted in NRC and were presently staying in Thane block were included in the study. Complete enumeration method was used . A Total Sample size of 96(based on the inclusion criteria) was obtained for the purpose of record based data, while for interview sample size was 73(20 cases were non traceable and 3 death were reported) with the parents/guardians of the children. Data was collected using a pre-validated semi structured interview guide via face to face interview. The study was conducted during the 18 month period from March 2017 to August 2018. Data was analysed by using SPSS software version 22.0. Results: Majority of the children admitted to the NRC were male (55.2%). Majority of the mothers were educated till middle school (34.3%) as were the majority fathers (37%). Majority of children had birth order 3 (76.7%). Acute respiratory infection (34.4%), acute gastroenteritis (26%) and acute febrile illness (19.8%) were the most common comorbidities observed among the children. Pre-lacteal feed was given in 5.1% children and colostrum was given to 56.1%, exclusive breast feeding was not done in majority of the children (65.8%).Conclusion: Severe acute malnutrition appears to be more prevalent among households belonging to middle and lower middle class. Educational status of parents was found to be low among majority of the study participants. Exclusive breast feeding was also lacking in majority of the children.